Perceived Level of Awareness of Green Residential Building Benefits among the Homebuyers in Sarawak - Ahmad Zaini, Afzan; Yaakub, Zul Azman; Tang, Anny Jia Siew; Khairul Hisham, Nur Khairina; Abd Aziz, Nurul Nadia (International Journal of Sustainable Construction Engineering and Technology, 2025)
Green residential buildings (GRBs) have been widely introduced as one of the most effective methods to cope with the issue of global warming. However, the development of GRBs in Malaysia is in an imbalance state whereby none of it has been developed in Sarawak. This might be due to the low awareness level and many homebuyers are reluctant to pay the higher cost for GRBs. Thus, the objective of this paper is to examine the awareness level of Sarawak homebuyers towards the benefits of GRBs. Quantitative methodology via questionnaire survey was employed to collect data from 200 respondents and Statistical Package for the Social Sciences (SPSS) was used for data analysis. The results indicated that the majority of Sarawak homebuyers are highly aware of the environmental benefits rather than the socioeconomic benefits of GRBs. Such findings can become a meaningful insight for the awareness and readiness of potential homebuyers in accepting the green concept for their future residential properties.